Decision Support System for Business Location Selection using the AHP Method Based on Android - Hizkia Hendra Rianingsih; Widyastuti Andriyani (P3M Politeknik Negeri Bengkalis, 2025)
The selection of a strategic business location is a crucial factor in the success of an enterprise. However, the decision-making process for choosing a location often involves various complex criteria that require careful analysis. This study aims to develop an Android-based Decision Support System (DSS) to assist entrepreneurs in selecting an optimal business location using the Analytical Hierarchy Process (AHP) method. AHP is chosen for its ability to break down complex problems into a hierarchy and quantitatively evaluate each criterion. The system is designed to allow users to easily access and operate the DSS through mobile devices. The criteria used in the location selection process include accessibility, cost, demographics, competition, security, infrastructure, regulations, and growth potential. Each criterion is weighted using pairwise comparisons, enabling objective and comprehensive assessments. The Android-based implementation allows for flexibility, enabling users to make decisions efficiently anytime and anywhere. System testing results indicate that the application can provide accurate business location recommendations based on the desired criteria, and it features a user-friendly interface. This Android-based DSS is expected to be a practical solution for supporting business decision-making processes quickly and accurately.